Diffuse Cutaneous Mucinosis in Dermatomyositis: A Case Report and Review of the Literature - Alexandra Caitlin Perel-Winkler; Chris T. Derk (Hindawi Limited, 2014)
We present the case of a patient with dermatomyositis and diffuse cutaneous mucinosis and give an up-to-date detailed review of all the published cases in the English literature describing the demographics, clinical picture, pathology management, and outcomes of this unique group of patients.